2018
DOI: 10.1016/j.jmii.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Clonal spread of carbapenem-resistant Acinetobacter baumannii across a community hospital and its affiliated long-term care facilities: A cross sectional study

Abstract: Twenty one subjects were enrolled. The major hospital admission diagnoses among the 21 subjects were pneumonia (71.4%). Genotyping of CRAB isolates by Rep-PCR revealed that a major clone, designated as type III, comprised fifteen of 21 (71.4%) isolates taken from 5 LTCFs and one study hospital. The isolates with type III were subtyped by PubMLST into 4 ST types. The most prevalent bla genes in these isolates were bla-like (85.70%, 18/21). Twenty isolates carried bla CONCLUSION: Clonal spread of bla-carrying CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…A. baumannii, which are nosocomial pathogens usually transmitted from the medical environment (patient, medical staff, or medical device). Several studies have shown that A. baumannii can spread between hospitals [40,41], which means the prevalence of ST2 is more serious in this region, not just the hospital involved in this study.…”
Section: Discussionmentioning
confidence: 87%
“…A. baumannii, which are nosocomial pathogens usually transmitted from the medical environment (patient, medical staff, or medical device). Several studies have shown that A. baumannii can spread between hospitals [40,41], which means the prevalence of ST2 is more serious in this region, not just the hospital involved in this study.…”
Section: Discussionmentioning
confidence: 87%
“…Of notice, A. baumannii usually comes from the medical environment (patient, medical staff or medical device). Several studies have shown that A. baumannii can spread between hospitals [2,21], which means the prevalence of ST2 is more serious in this region, may not just the hospitals involved in this study.…”
Section: Discussionmentioning
confidence: 92%
“…However, several decades passed without significant innovations until the discovery and development of oxazolidinones in 2010 (Figure 1). Moreover, the continuous uncontrolled use of these medicines favored the rapid spread of resistant pathogens, where new compounds were discovered, and their introduction into clinical practice was not fast enough [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The CDC (Centers for Disease Control and Prevention) has recognized the emerging antibiotic resistance as a significant threat to public health [8]. Superbugs, such as Methicillin-resistant Staphylococcus aureus (MRSA), show antibiotic resistance rates that surpass 50% in 5 out of 6 world regions; in contrast, the multidrugresistant Acinetobacter baumannii, described as a dangerous agent by the Society of Infectious Diseases of America (SIDA), is a notable threat in intensive care units (ICUs) due to the development of resistance to broad-spectrum antibiotics [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%